The exploration of social capital and its relation with economic empowerment of Orang Kuala in Johor, Malaysia - Amir Zal, W. A.; Redzuan, Ma’rof; Abu Samah, Asnarukhadi; Hamsan, Hanina Halimatusaadiah (Universiti Putra Malaysia Press, 2013)
Trust economic empowerment is an issue that is rarely debated in discussing the reality of Orang Asli’s economy. Instead, other issues such as lagging behind, poverty, and marginalization of Orang Asli often become the hot topics for discussion. History, however, has shown that Orang Asli have been conducting economic activities with other communities for ages, even though the returns of the aforementioned activities are not encouraging for them. Orang Asli also have shown, through their history, their ability to fulfil other communities’ needs. Such a relationship directly indicates the relation of social capitals and economic empowerment among Orang Asli. In order to examine this issue, a study was carried out. The study was conducted on seven interviewees, who are the Orang Kuala villagers, residing at Bumiputera Dalam, Batu Pahat, Johor, Malaysia. Data were gathered by using in-depth interview method and semi-structured interview protocol technique. Data gathered were then analysed by using QSR NVivo software. The findings of this study showed that Orang Kuala have social capitals but the relationship differs according to the types of social capital, the bonding social and the bridging social capital. In particular, Orang Kuala have weak bonding social capital but possess a strong bridging social capital. They also show the ability to empower their economy through self-reliant, participation in businesses, increase in revenues and ability to control their income. As a conclusion, this study concluded that the economic empowerment of Orang Kuala is a result of bridging social capital.